Macroeconomics Policy and the Europeran Union Accession: Albanian Case - Imeraj, Erinda (Richtmann Publishing, 2012)
The purpose of this paper is the analyze of the Albanian macroeconomic situation, its developments and policies through thechallenging way to the EU accession. Albania was the last of the central and eastern European countries to embark on democratic andfree market reforms. Although it might be early to say that everything was done in the proper way to establish the new market economy,Albania is seriously involved in this transformation and has the chances to join Europe, and furthermore the worldwide economiccommunity. Albanian’s economic performance shows success story with many ups and downs. Even though Albanian economy hasimproved substantially over years and outperformed many other countries in the Balkan region, according to major income indicator westill remain the poorest country in Europe. Trying to be part of EU, Albania still has to perform many structural reforms withmacroeconomic and fiscal frameworks. A long way in reducing macroeconomic imbalances such as external deficit and the highunemployment rate but also following a prudent monetary policy by reaching and maintain price stability and strengthening thesurveillance of financial system. It will be concluded that the developments of Albanian economy to fulfill the EU conditions, even thoughin difficult situations, will lead on a proper way to the important goal, the EU accession, but would have the positive impact on Albaniangrowth. This paper is based on real and official data taken from INSTAT and World Bank, which will be theoretically analyzed and it willtake place also a regression analyze.